Penalaran Hukum Dalam Kritik Ilmu - Dwi Primilono Adi (Fakultas Hukum Universitas Mataram, 2015)
Jurisprudence in knowledge science philosophy goes into science that based on the ratio in order the truth that found must base on using deductive logic and to get the truth must coherent. Law is not a tangible things, but it is the concept. as a concept, law will be in abstract area, where all of empirical science can’t be able to get it easily. In the abstract area, discourse of law is a discourse of philosophy, or at least from a discourse of philosophy. It is right what the people said that concept is result of perception, but processing of result perception (subjective and individual) to a concept (collective and intersubjective) base on a paradigm that assumed as a root of together thinking, whatever the assumption. Thus, it is to be clear that the law has prescriptive character or normative which base on the ratio, where constructed base on the perception concept. Reasoning that done must use deductive logic, whereas the truth which gotten is coherent. Law as a concept will be in nomenon area and not in phenomenon area.